Control of Seed Germination and Plant Development by Carbon and Nitrogen Availability - Osuna, Daniel; Prieto, Pilar; Aguilar, Miguel (Frontiers in Plant Science, 2015)
Little is known about the molecular basis of the influence of external carbon/nitrogen (C/N) ratio and other abiotic factors on phytohormones regulation during seed germination and plant developmental processes, and the identification of elements that participate in this response is essential to understand plant nutrient perception and signaling. Sugars (sucrose, glucose) and nitrate not only act as nutrients but also as signaling molecules in plant development. A connection between changes in auxin transport and nitrate signal transduction has been reported in Arabidopsis thaliana through the NRT1.1, a nitrate sensor and transporter that also functions as a repressor of lateral root growth under low concentrations of nitrate by promoting auxin transport. Nitrate inhibits the elongation of lateral roots, but this effect is significantly reduced in abscisic acid (ABA)-insensitive mutants, what suggests that ABA might mediate the inhibition of lateral root elongation by nitrate. Gibberellin (GA) biosynthesis has been also related to nitrate level in seed germination and its requirement is determined by embryonic ABA. These mechanisms connect nutrients and hormones signaling during seed germination and plant development. Thus, the genetic identification of the molecular components involved in nutrients-dependent pathways would help to elucidate the potential crosstalk between nutrients, nitric oxide (NO) and phytohormones (ABA, auxins and GAs) in seed germination and plant development. In this review we focus on changes in C and N levels and how they control seed germination and plant developmental processes through the interaction with other plant growth regulators, such as phytohormones.